2008
DOI: 10.1002/elps.200700852
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the migration behavior of rabbit liver apothioneins in capillary electrophoresis

Abstract: Metallothioneins (MTs) are a group of low-molecular-mass proteins (6-7 kDa) characterized by their great affinity for heavy metal ions. At acidic pH, the bound metal ions are released from the amino acidic structure and MTs lead to apothioneins. In this study, a general equation is used to model the electrophoretic mobility of rabbit liver apothioneins as a function of the pH of the separation electrolyte. The ability of these relationships to explain the migration behavior of these relatively complex polyprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…In a previous study, we found that the classical polymer model (a 5 1/2) yielded excellent correlations when it was employed to study the m e of several peptide hormones and neuropeptides over the pH range between 2 and 12 in aqueous media [10,16]. Several other authors have drawn similar conclusions for different sets of peptides using the Stoke's law, the Offord's surface area law or minor modifications derived from any of the three [1,2,[9][10][11][12][13][14][15][16][17][18]. Several modifications have been suggested to these classical relationships, but in our opinion the classical formulations still providing the best results in the whole pH range [9,10,16].…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…In a previous study, we found that the classical polymer model (a 5 1/2) yielded excellent correlations when it was employed to study the m e of several peptide hormones and neuropeptides over the pH range between 2 and 12 in aqueous media [10,16]. Several other authors have drawn similar conclusions for different sets of peptides using the Stoke's law, the Offord's surface area law or minor modifications derived from any of the three [1,2,[9][10][11][12][13][14][15][16][17][18]. Several modifications have been suggested to these classical relationships, but in our opinion the classical formulations still providing the best results in the whole pH range [9,10,16].…”
Section: Resultsmentioning
confidence: 60%
“…The classical semiempirical relationships, which relate electrophoretic mobility and charge-to-mass ratio (m e versus q/M a ), have been extensively used to explain migration behavior of peptides and proteins [1,2,[9][10][11][12][13][14][15][16][17][18]. In general, the m e of a peptide is proportional to its q and inversely proportional to its Stoke's radius (r).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations